Contratos de integração no sistema agroindustrial avícola nas cooperativas no Oeste do Paraná: formalidade e confiança - Silveira, Tânia Maria Smaniotto (2017)
This thesis deals with the dynamics of the integration contracts present in the Poultry Agroindustrial System (SAA), which intermediate the productive integration between processors cooperatives and integrated poultry producers in the West region of Paraná. As thesis object, analyzes the evolution of clauses of the governance structure poultry partnership agreement. In this sense, structural changes and the institutional environment in the Brazilian economy were considered, as well as the relationships established between agents in the context of integration contract. Therefore, the objective is to analyze the historical trajectory of the contracts of poultry integration in agroindustrial cooperatives, over time, in the west region of Paraná. The theoretical reference used was based on the analysis of the New Institutional Economics (NEI) and its conceptual developments, and also on Toulemon's (1945) thesis. It was initially assumed that the governance structure of the poultry partnership agreement of the West Paraná agricultural cooperatives has come over the decades, incorporating new clauses to adapt to the Brazilian economic and institutional changes and the transformations inherent in the SAA. As part of this process, a strong and narrow productive link was established and consolidated. Thus, the inherent dimensions of contracts are crossed by the relationship of mutual trust established between the parties involved. The contracts are signed, but they are configured as formality. The sworn faith and the word given are the amalgam that unites the free wills of the agents involved in integrated production. As for methodological procedures, primary research was carried out with the 5 agroindustrial cooperatives in the West region of Paraná, and 282 questionnaires were applied to integrated poultry farmers, seeking to understand the asymmetries between the efficiency or formality of poultry contracts. The results show that the SAA maintains its structure based on the contracts, that is, the contractual formalities are important, but it was possible to observe that the performance of the Poultry SAA is the result of consolidated trust relationships over the 30 years of the activity. It is hoped that this work will contribute to the understanding of the coexistence of contractual formality in the SAA in the agroindustrial cooperatives of the West region of Paraná, and the strong bonds of mutual trust consolidated between integrating cooperatives and integrated poultry producers, an amalgam of activity efficiency.